2018
DOI: 10.1111/apt.14493
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: psychosocial factors associated with pain in inflammatory bowel disease

Abstract: Psychosocial factors appear to play a significant role in IBD-pain. Further research is required to explore psychosocial constructs in relation to IBD-pain, with use of validated pain measures, large sample sizes and clearer characterisation of disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 76 publications
7
63
1
2
Order By: Relevance
“…Various symptoms not directly related to intestinal inflammation have been found to impact on patient-reported outcomes and may, therefore, be of importance in patient management. A recent review has demonstrated several psychological factors to be associated with pain in IBD patients and that such factors remain important regardless of disease activity [9]. Although we found that depressive and anxiety symptoms were not independently associated with pain severity in multivariate analyses, these symptoms may be of importance in some patients [7,9].…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Various symptoms not directly related to intestinal inflammation have been found to impact on patient-reported outcomes and may, therefore, be of importance in patient management. A recent review has demonstrated several psychological factors to be associated with pain in IBD patients and that such factors remain important regardless of disease activity [9]. Although we found that depressive and anxiety symptoms were not independently associated with pain severity in multivariate analyses, these symptoms may be of importance in some patients [7,9].…”
Section: Discussioncontrasting
confidence: 69%
“…Modulating factors, including different psychological factors, may significantly contribute to the clinical manifestation and severity of pain [7][8][9]. Emotional problems and inadequate coping mechanisms have been associated with development of chronic pain syndromes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Poor mental health has also been previously reported as a significant predictor of hospitalization, readmission, and increased risk of surgery in those with IBD. Pain, fatigue, and opioid use are also known to be associated with poor mental health in IBD . Therefore, our findings demonstrate that high rates of distress are likely to contribute to the burden of IBD at the personal and societal levels and translate into large costs of IBD care in Australia…”
Section: Discussionmentioning
confidence: 70%
“…Pain, fatigue, and opioid use are also known to be associated with poor mental health in IBD. [30][31][32][33] Therefore, our findings demonstrate that high rates of distress are likely to contribute to the burden of IBD at the personal and societal levels and translate into large costs of IBD care in Australia. 1 The limitations of this survey have been previously discussed 17 and include the following: its online nature, which precluded an objective assessment of IBD status and disease activity; a female-predominant sample of people aged 16 years and older excluded the pediatric population and limited the generalizability of its findings; and a low participation rate from people in remote areas.…”
Section: Discussionmentioning
confidence: 74%
“…1 Patients with IBD suffer physical discomfort, which is often accompanied by depression, anxiety, sleep disorders, and other mental and psychological problems. [2][3][4] IBD arthritis (IBDA) is arthritis associated with IBD, which is the most common parenteral manifestation of IBD. Roughly 15% to 20% of the patients with IBD may have arthralgia or arthritis.…”
mentioning
confidence: 99%